Energy-efficient building design in Southeast Europe - Jovanović, Vladimir (Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2019)
The aim of the book is to improve conventional building design in Southeast Europe. This is done with proposing conceptual guidelines for designing energy-efficient buildings for different geographic regions of Serbia. The focus is on climate-appropriate design of building envelopes. To adress sustainability, economical, environmental and social aspects are evaluated. The body is divided into three main chapters: traditional houses, the existing housing stock, and design patterns for future buildings. The conclusions and the methodology can be applied in the rest of Southeast Europe, since Serbia has a unique position in the middle of the region, covering different geographical areas that spread far out of Serbia's borders. Contents Introduction - Traditional Homes - Refurbishing Existing Building Stock - Future Housing Designs - Conclusion Audience Students and Researcher focusing on energy-efficiency, Professionals working on building projects in Southeast Europe Author Dr. techn. Vladimir Jovanović, Architect with a focus on energy-efficient and sustainable building design.